Penerapan Model Pembelajaran Tipe Jigsaw untuk Meningkatkan Keterampilan Komunikasi dan Hasil Belajar Kognitif Siswa Kelas VII - Sulastini, Widia (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
The research aims to improve the communication skills and cognitive learning outcomes of class VII students at SMP Negeri 5 Kopang. The type of research is Classroom Action Research (CAR). The instruments used are observation sheets which are used to observe or determine communication skills and implementation of learning during the learning process, and tests/questions are used to determine students' understanding of the lessons given using the jigsaw type learning model during the teaching and learning process. The research results show an increase, both in terms of communication skills and cognitive learning outcomes. The results of the analysis of the percentage of communication skills of students in the first cycle at the first meeting, the indicator of ability to work together in groups was 18% in the very poor category, at the second meeting the percentage was 31% in the poor category, while in the second cycle at the first meeting the percentage was 72% in the good category, and at the second meeting the percentage was found to be 77% in the good category. Indicators of verbal communication skills were the results of students' communication skills in cycle I at meeting I with a percentage of 22% in the poor category, at meeting II with a percentage of 41% in the quite good category, while in cycle II in meeting I the percentage was 63% in the good category, and at the second meeting, the percentage was found to be 72% in the good category. The indicator of the ability to respect friends' opinions was the result of students' communication skills in cycle I with a percentage of 18% in the very poor category, in meeting II with a percentage of 45% in the quite good category, while in cycle II in meeting I the percentage was 72% in the good category, and in meeting II with a percentage of 81% in the very good category. The results of student learning evaluations in cycle I achieved classical completeness with a percentage of 59% with an average value of 68.6, and in cycle II classical completeness with a percentage of 90% with an average value of 82.2. The conclusion from the research results is that the jigsaw type learning model can improve communication skills and cognitive learning outcomes for class VII students at SMP Negeri 5 Kopang.